The effect of motor relearning on balance, mobility and performance of activities of daily living among post-stroke patients: Study protocol for a randomised controlled trial. (March 2022) - Ghrouz, Amer; Marco, Ester; Muñoz-Redondo, Elena; Boza, Roser; Ramirez-Fuentes, Cindry; Duarte, Esther
Background: Balance and gait impairments are the most common motor deficits due to stroke, limiting the patients' daily life activities and participation in society. Studies investigating effect of task-specific training using biomechanical balance and gait variables (i.e. kinetic and kinematic parameters) as well as posturography after stroke are scarce. Objectives: The primary aim of this study is to assess the efficacy and long-term outcome of task-specific training based on motor relearning program (MRP) on balance, mobility and performance of activities of daily living among post-stroke patients. Methods: In this two-armed randomised controlled clinical trial, a total of 66 sub-acute stroke patients who meet the trial criteria will be recruited. The patients will randomly receive task-specific training based on MRP or a conventional physical therapy program (CPT). Twenty-four physiotherapy sessions will be conducted, divided into three training sessions per week, 1 h per session, for 8 weeks, followed by an analysis of changes in patient's balance, gait and performance of activates of daily living at three time periods; baseline, post-intervention and follow-up after 3-months, using clinical outcome measures and instrumental analysis of balance and gait. Discussion: The results of this study can guide to better understanding and provide an objective clinical basis for the use of task-specific training in stroke rehabilitation. Also, it intends to help bridge the current knowledge gap in rehabilitation and training recommendations to provide a therapeutic plan in post-stroke rehabilitation. Trial registration: ClinicalTrials.gov (NCT05076383). Registered on 13 October 2021 (Protocol version: v2.0).